2019
DOI: 10.18502/kss.v3i26.5391
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Trust within Information Quality and Price to Engage Impulsive Buying Behaviour to Generate Customer’s Repurchase Intention: A Case of M-Commerce in Indonesia (GoFood)

Abstract: The purpose of this study is to examine the customer’s impulsive buying behavior engage with trust, which involves price and information quality to determine the repurchase intention of the customers. The research model was analyzed using Regression Analysis by SPSS of 100 respondents who had previously completed the questionnaire. The proposed model and hypotheses are supported this study. Our findings that Price and Information Quality significantly influenced to Impulsive Buying in strong and significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
4
0
3
Order By: Relevance
“…In a previous study, Tam et al (2019) found that information quality significantly affects consumer satisfaction. Another study explained that information quality had a significant influence on repurchase intention (Prastiwi & Iswari, 2019). Thus, the hypotheses related to information quality are as follows: H3: Information quality positively influences customer satisfaction.…”
Section: Information Qualitymentioning
confidence: 98%
“…In a previous study, Tam et al (2019) found that information quality significantly affects consumer satisfaction. Another study explained that information quality had a significant influence on repurchase intention (Prastiwi & Iswari, 2019). Thus, the hypotheses related to information quality are as follows: H3: Information quality positively influences customer satisfaction.…”
Section: Information Qualitymentioning
confidence: 98%
“…Maka dapat disimpulkan bahwa hipotesis keenam tidak didukung. Hal ini tidak sejalan dengan penelitian sebelumnya (Prastiwi & Iswari, 2019) yang menyatakan bahwa kualitas informasi memiliki pengaruh yang positif terhadap niat pembelian ulang.…”
Section: Hasil Dan Pembahasanunclassified
“…Serta memiliki pernyataan jika tiap indikator dalam variabel rates terdapat kontribusi yang berpengaruh untuk mengukur variabel rates. Ditambah hasil pengujian ini juga sependapat dengan penelitian serupa dari (Yasri et al, 2020) serta (Prastiwi and Iswari, 2019), yaitu mengenai variabel tarif (rates) berpengaruh kepada repurchase intention melewati customer trust.…”
Section: Pembahasanunclassified